2000
DOI: 10.1177/000841740006700105
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Community Utility of the Canadian Occupational Performance Measure

Abstract: This study addressed the validity and community utility of the Canadian Occupational Performance Measure (COPM) (Law et al., 1991; 1994; 1998): a measure that now represents a national standard in clinical practice and research in occupational therapy in Canada. The study employed a crossectional design. Participants for the study were former consumers of occupational therapy services, recruited from the Queen's University catchment area (Kingston, North Bay, Oshawa, Perth, Peterborough). A sample of 61 disabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(163 citation statements)
references
References 17 publications
4
157
0
2
Order By: Relevance
“…Change in performance and satisfaction is measured by the difference in total scores over a period of time (Law et al, 1994;Phipps & Richardson, 2007). The COPM has sound construct and criterion validity and test-retest reliability of >.80 (Law et al, 1994(Law et al, , 2005McColl, Paterson, Davies, Doubt, & Law, 2000).…”
Section: Instrumentsmentioning
confidence: 99%
“…Change in performance and satisfaction is measured by the difference in total scores over a period of time (Law et al, 1994;Phipps & Richardson, 2007). The COPM has sound construct and criterion validity and test-retest reliability of >.80 (Law et al, 1994(Law et al, , 2005McColl, Paterson, Davies, Doubt, & Law, 2000).…”
Section: Instrumentsmentioning
confidence: 99%
“…14,15,17 Boschand McColl and colleagues established construct validity, 18,19 Ripat and colleagues established concurrent validity, 20 and several authors concluded that the COPM had satisfactory criterion validity. 18,19,21 In addition, face validity 18 and discriminant validity 22 have been established.…”
Section: Canadian Occupational Performance Measure (Copm)mentioning
confidence: 99%
“…The reproducibility of the performance and satisfaction scores was found to be poor for the individually identified problems and moderate to high for the scores averaged over all the problems identified by a client [7,[9][10][11][12][13]. Supportive evidence was found for the content, convergent, and divergent validities of the COPM [2,7,9,11,[13][14][15][16][17][18]. Clinical utility, evaluated in a number of different studies, supported the use of the COPM for a variety of clients in different settings [13,17,[19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 96%